Protein Digestion of Bromelain from Pineapple Waste on Beef Tendon Product - Yialee, Yanglao; Boulom, Sayvisene; Chanthavong, Souksavanh; saarth, See; Jiavang, Yethao; Xaynhiaxang, Somhak; Keopilar, Tingkham; Duangvongsa, Inpeng; Keosilaphet, Vilayphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The aims of this investigation are to extract the bromelain from pineapple waste and digest the protein in beef tendon. The concentrations of pineapple bromelain were dived to 3 levels such as 0, 10, 30 and 100% (v/v). The temperature of protein digestion was at 25 °C for 30 minutes. The chemical properties of pineapple peel and beef tendon were measured for ash, moisture, pH, protein, water activity, and water holding capacity. The final products were suggested for a sensory evaluation using 50 panelists. The results of protein, water holding capacity, pH, ash, moisture, and water activity in the digested beef tendon had a range of 2.45±0.41-8.33±1.49mg/L, 54.38±1.71-72.22±1.500%, 4.94±0.26-5.68±0.10, 8.22±1.17-13.38±1.10%, 69.82±9.45-79.36±6.37% and 0.97±0.00-0.98±0.01, respectively. Bromelain from pineapple peel digested protein around 4.28±0.41-8.33±0.51% on the beef tendon. The highest percent of protein digestion was at 100%. However, the effecting of protein digestion from 30 and 100% were not significantly on the statistic (P>0.05). For the sensory evaluation, the bromelain concentration of 30 and 100% showed highest scores for overall acceptability, Softness and fatness. For the control or no addition of bromelain showed the lowest scores for odor and roughness. Bromelain from pineapple peel is recommended for protein digestion and softness in meat products on household producers or food industry.